Sistematización del diseño e implementación del manual de funciones de la Empresa Fundry Metal. - Rodriguez Montenegro, Lenin Omar (2018)
The current business management model has focused its goals in planning its strategies in order to optimize the material and financial resources to obtain inflows at the lowest possible cost, often neglecting the attention that human talent deserves, which is not only significant for achieve business success, but are the main engine of it. Therefore, the competencies of employees must be attended and improved so that they show their competencies in each one of their functions that make up their position. Every company requires a guide that allows reaching its objectives and goals; for this it requires the support of its collaborators same ones that must interact with each other. An instrument that will make it possible to have a structure that will show the employees what is required is the Function’s Manual. The development of this work corresponds to the systematization, design and implementation of a Function's Manual for the company FUNDRY METAL, Metal Foundries, with the objective of improving and serving as a guide on the structuring of the positions of the company to keep in mind the operation of the company to which its collaborators belong, promoting the responsibility and quality of the products and services we offer, focusing on growing and being competitive in the market of metal foundries in our country.